Developing Professional Creativity of Teachers Based on Problem Based Learning (PBL) - Pozilova, Shakhnoza Khaydaraliyevna (Tecno Scientifica Publisher, 2023)
The article determined the importance and problems of developing the professional creativity of teachers of professional educational institutions in professional training courses. Moreover, the article described the method of conducting practical training based on PBL, and as a result, the indicators of the evaluation criteria were given. The purpose of the article was the methodology of practical training organized on the basis of PBL to increase the professional creativity of teachers of professional education in training courses. Innovative-methodical projects were developed for improving teachers' professional creativity, and creative educational technologies and methods were used at each stage. Based on the mathematical and statistical analysis of the research, the types of personal and professional creativity of teachers were determined and the concept of professional creativity was revealed. A module aimed at enhancing the professional creativity of teachers was included in the curriculum of personnel retraining and professional development courses, and didactic support was developed with helping creative techniques and platforms which were helpful for assessing creative abilities of teachers. As a result, the professional creativity of teachers of vocational education was enhanced by 10%.